Recurrent tetanus in a donkey. (4th November 2021) - Kay, G.; Souhail, M. L.; Mazan, M.
Summary: This report describes a case of a non‐lethal tetanus in a donkey that re‐presented 9 months after discharge with a second episode of tetanus. This is the first time "recurrent" tetanus has been reported in equids, although it is a recognised, albeit rare occurrence in humans. This case illustrates the fact that natural infection did not confer immunity in this particular donkey. This highlights the importance of tetanus toxoid vaccination even for animals that recover from the disease.